Optimalisasi Sinkronisasi Data SKP Untuk Mendukung Pengurusan SIP Tenaga Kesehatan di Kota Pekanbaru - Diah Elvira Syafruddin; Jasrida Yunita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Synchronization of Professional Credit Unit (SKP) data is an essential component in the process of renewing Practice Licenses (SIP) for health workers. The problem identified in Pekanbaru City was the inconsistency of SKP data between the SatuSehat SDMK platform and the Ministry of Health SKP system, which caused obstacles in the SIP renewal process for health workers. This condition affected the legality of professional practice and potentially disrupted the continuity of healthcare services in healthcare facilities. This activity aimed to identify the management of health human resources at the Pekanbaru City Health Office and to analyze problems related to SKP data synchronization in the SIP renewal process. The method used was a residency approach through observation, interviews, document review, and analysis using the Urgency, Seriousness, Growth (USG) method and Fishbone Analysis to determine problem priorities and identify the causes of data inconsistency. The activity was conducted from November 11 to November 28, 2024, at the Pekanbaru City Health Office. The results showed that the digitalization of SIP administration had improved the efficiency of administrative services for health workers. However, technical problems in SKP data integration were still identified. Contributing factors included system integration issues, limited user understanding of digital platforms, and suboptimal coordination in data reporting. Proposed solutions included periodic reporting to the Ministry of Health, official correspondence regarding integration problems, and the implementation of socialization and technical guidance on digital platform utilization. These interventions are expected to improve the transparency, accuracy, and reliability of the information system in the SIP renewal process for health workers